Ectopic lacrimal gland in the lacrimal sac mimicking tumour: literature review. Issue 7 (22nd July 2020) - Saratziotis, Athanasios; Zanotti, Claudia; Baldovin, Maria; Emanuelli, Enzo
Abstract : An 80-year-old man referred with repeated episode of dacryocystitis from the left lacrimal drainage system and palpable swelling. For many years, he has being presented with epiphora unilaterally with chronic dacryocystitis. Investigations with dye-test revealed subocclusion of the natural passage of the tears, and CT and MRI scans revealed solid mass in the lacrimal sac. The lacrimal sac was opened by endonasal endoscopic approach, the sacral mass was identified and completely removed. The histopathological examination showed lacrimal gland in ectopic position. Patient followed for 18 months with complete recovery of symptoms. In our differential diagnosis, the ectopic lacrimal gland is also identified, when a mass in the lacrimal sac and duct is present. Successful surgical excision required considerable multidisciplinary teamwork between ophtalmologist–ENT (Otolaryngologist) and radiologist. Endonasal endoscopic approach is perfectly safe with direct control and ensures a smooth postoperative recovery.